Landscape image H.A.C.K. Human Activity Captured Kernels - Bimbao, Jose Antonio P. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/7358/6422